Getting respect responding to stigma and discrimination in the United States, Brazil, and Israel - Lamont, Michèle 1957-; Silva, Graziella Moraes Dias da 1976-; Paige, Jessica Welburn; Guetzkow, Joshua A. 1974-; Mizrachi, Nissim 1962-; Hertsog, Ḥanah 1946-; Reis, Elisa P. 1946- (Princeton University Press, 2016)
"Racism is a common occurrence for members of marginalized groups around the world. Getting Respect illuminates their experiences by comparing three countries with enduring group boundaries: the United States, Brazil and Israel. The authors delve into what kinds of stigmatizing or discriminatory incidents individuals encounter in each country, how they respond to these occurrences, and what they view as the best strategy--whether individually, collectively, through confrontation, or through self-improvement--for dealing with such events. This deeply collaborative and integrated study draws on more than four hundred in-depth interviews with middle- and working-class men and women residing in and around multiethnic cities--New York City, Rio de Janeiro, and Tel Aviv--to compare the discriminatory experiences of African Americans, black Brazilians, and Arab Palestinian citizens of Israel, as well as Israeli Ethiopian Jews and Mizrahi (Sephardic) Jews"-- dust jacket front flap
Keywords: Discrimination / United States; Discrimination / Brazil; Discrimination / Israel; Discrimination; Diskriminierung; Arbeiterklasse; Mittelstand; Brazil; Israel; United States; Brasilien; USA; Tel Aviv; Rio de Janeiro; New York, NY